The Emerging Role of Altered Cerebellar Synaptic Processing in Alzheimer’s Disease - Hoxha, Eriola; Lippiello, Pellegrino; Zurlo, Fabio; Balbo, Ilaria; Santamaria, Rita; Tempia, Filippo; Miniaci, Maria Concetta (Frontiers in Aging Neuroscience, 2018)
The role of the cerebellum in Alzheimer’s disease (AD) has been neglected for a long time. Recent studies carried out using transgenic mouse models have demonstrated that amyloid-β (Aβ) is deposited in the cerebellum and affects synaptic transmission and plasticity, sometimes before plaque formation. A wide variability of motor phenotype has been observed in the different murine models of AD, without a consistent correlation with the extent of cerebellar histopathological changes or with cognitive deficits. The loss of noradrenergic drive may contribute to the impairment of cerebellar synaptic function and motor learning observed in these mice. Furthermore, cerebellar neurons, particularly granule cells, have been used as in vitro model of Aβ-induced neuronal damage. An unexpected conclusion is that the cerebellum, for a long time thought to be somehow protected from AD pathology, is actually considered as a region vulnerable to Aβ toxic damage, even at the early stage of the disease, with consequences on motor performance.